Protocolos de treinamento na musculação equiparados pelo tempo sob tensão provocam alterações similares na força e hipertrofia muscular - Hugo Cesar Martins Costa (2017)
Resistance training protocols equated by time under tension (TUT), but configurated with different repetition numbers and repetition durations, elicit distinct acute neuromuscular responses. However, it is not yet clear whether such protocols promote different increases in strength and muscle mass after a training period The present study aimed: (i) to evaluate the effect of two training protocols equated by TUT in the increase of cross sectional area (total and regional) of the muscles pectoralis major and triceps brachii; (b) to verify the impact of those protocols on the performance of one maximum repetition test (1RM), strength endurance (SE), and maximum isometric voluntary contractions (MIVC) performed in different ranges of motion. Thirty-tree male subjects who did not perform strength training at least the last six months were divided into three groups: two experimental (Protocols A and B) and a Control group (no training). The protocols performed by each experimental group (10 weeks) were differentiated by the number of repetitions (6 or 12) and repetition durations (6s or 3s), but equated by TUT (36s per set), number of sets (3-4), intensity (50-55% of 1RM) and rest interval (3 min). Protocol A was characterized by higher number of repetitions and shorter duration of repetition (12 repetitions, 3s repetition duration), while Protocol B had lower number of repetitions and longer duration of repetition (6 repetitions, 3s repetition duration). The training and strength tests occurred in smith machine bench press. After data collection, analysis of variance was applied to all variables, adopting a level of significance of 0.05. The experimental groups demonstrated an increase in total and regional muscle cross sectional areas when compared to the Control group, but without differences between Protocols A and B. No differences were found in regional hypertrophy of the pectoralis major muscle, but in the triceps brachii muscle, the gain in the distal region was higher when compared to the middle and proximal regions. The experimental groups obtained similar increases in the 1RM, SE, and MIVC tests, but higher than the Control group. We conclude that training protocols with the same TUT promote similar strength gains and muscle hypertrophy. In addition, performing the bench press exercise causes non-homogeneous hypertrophic changes along the length of the triceps brachii muscle.